Genetic characterization using microsatellites of Creole and Holstein cattle from the high southern tropics of Ecuador - Méndez, Silvana (2024)
The aim of this study was to analyse the gene and genotypic parameters using microsatellites of Creole bovine (CB) from the high southern tropics of Ecuador and contrasting them with registered Holstein bovine (HB); For this, blood was collected from 7 CC and 3 BC subpopulations. Fifteen markers grouped into 4 mixtures were analysed; 1) CSRM60, INRA083, CSSM66; 2) ETH3, HEL9, TGLA53, BM1818, ILSTS006; 3) BM2113, ETH225, TGLA122, ETH10; and 4) TGLA227, INRA032, SPS115. Genetic variation parameters were determined: number of alleles (Na), number of effective alleles (Ne), frequency of null alleles (f-Null), observed heterozygosity (Ho) and expected (He), Polymorphism Information Content (PIC), inbreeding coefficients (Fis), Hardy-Weinberg equilibrium (HWe). In addition, a dendrogram was constructed based on Nei’s distances and identities, and finally, the AMOVA multilocus analysis. In most of the loci, the CB presented a higher number of Na and Ne than the HB. Some markers do not have HWe. Regarding Ho, there was no significant difference between BC and BH, except for the ETH3 marker. In the dendrogram, the BC and BH subpopulations were in two groups on nearby branches of the tree, but well differentiated from each other. A variance percentage of 6% was found between subpopulations. In conclusion, BC differ from BH in a greater number of alleles in 80% of the markers and high heterozygosity. In addition, the BC and BH populations show defined phylogenetic distances. The ETH3 marker allows to clearly differentiate BC from BH.